The coldest trail [large type] - Dundee, Wayne D. (Dundee, Wayne D. Lone McGantry western, 2023)
"Months have passed since five ruthless men killed Lone McGantry's partner and stole the horses from their ranch. Now, finally free of obligations that have kept him from taking up pursuit sooner, Lone has set out on a cold trail to track down the killers and make them pay. He'd prefer revenge, he'll settle for justice . . . But the trail is not only cold, it is twisty and marked by dangers at every turn, even apart from the quarry he is after. Lone will have to fight and shoot his way through these menacing obstacles and threats to his own life before the real prey is finally in his gunsights."--